Effect of Shallow Cryogenıc Heat Treatment on Metal Inert Gas Weldıng Zone of S 355 J2 Steel - Zafer Özdemir (Politeknik Negeri Lhokseumawe, 2023)
Metal inert gas welding (MIG) is generally conducted in the pressure vessel industry due to its high quality and easy automation. S355 J2 steel is used widely in this industry for its proper welding properties. To carry out and obtain high melting efficiency for satisfactory mechanical properties according to welding parameters, sometimes heat treatment is applied to materials, but generally it is not common in welding industry. In this study the effect of conventional heat treatment and shallow cryogenic heat treatment effects to the mechanical properties of welding zone of S 355 J2 steel welded with MIG is investigated. The charpy impact tests have been carried out. The welding plate is prepared according to this purpose and it is cut for impact test samples 10 X 10 x 55 mm. Totally 30 samples are prepared for 5 processes. Process 1: 6 samples for without heat treatment. Process 2: 6 samples for normalization-quenching in water. Process 3: 6 samples for normalization-quenching-tempering. Process:4 6 samples for normalization-shallow cryogenic treatment. Process 5: 6 samples for normalization-shallow cryogenic treatment-tempering. Notch of impact test samples are prepared just in the middle of the welding zone (2 sample for each process) , HAZ (2 sample for each process) and basemetal (2 sample for each process). The hardness values are taken from base metal, heat affected zone and welding area respectively. Hardness values and impact test results are compared. As a result, generally, it has been observed that shallow cryogenic heat treatment have a remarkable effect on toughness, despite a little decrease in hardness. The toughness of welding zone is increased approximately %40 and HAZ % 5 after cryogenic heat treatment. The hardness of WZ is increased approximately % 5 after cryogenic heat treatment, no significant change is observed in HAZ.